ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, BOPO, NET INTEREST MARGIN, DAN LOAN TO DEPOSIT RATIO TERHADAP PERUBAHAN LABA - MS, Nur Artwenda; Prasetiono, Prasetiono (Universitas Muhammadiyah Magelang, 2009)
This research is performed in order to test the influence of the variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Biaya Operasi Pendapatan (BOPO), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR), toward Earning Changes. Sampling technique used is purposive sampling with criteria as General Banking in Indonesia who provide financial report and traded during period 2004 through 2007 and forwarded to Bank Indonesia. The Data is based on publicity Indonesia Banking Directory since 2004 to 2007. Obtained by amount sampel as much 102 company from 136 banking company in Indonesia 2004-2007 period. Analysis technique used is doubled regression with smallest square equation and hypothesis test use t-statistic to test coefficient of regression partial and also f-statistic to test the truth of collectively influence in level of significance 5%. Others also done a classic assumption test covering normality test, multicolinierity test, heteroscedastisity test and autocorrelation test. During research period show as data research was normally distributed. Based on multicolinierity test, heteroscedasticity test and autocorrelation test variable digressing of classic assumption has not founded, its indicate that the available data has fulfill the condition to use multi linier regression model. From the result of analyse indicate that data CAR, NIM, NPL, and BOPO in partial significant toward earning changes big bank, while only BOPO and NIM have an significant effect to Earning Changes small bank.